Islamization of Sylhet-Cachar Region in Precolonial period: A Historical Study - Uddin Ahmed, Ohi (International Journal of Psychosocial Rehabilitation, 2020)
The spread of Islam in India has been studied in the context of some conventional theories. East Bengal and West Punjab, where large-scale conversion to Islam took place among the indigenous people, were not experienced elsewhere in the subcontinent. Therefore, the conventional theories seem inappropriate in examining the spread of Islam in East Bengal. The Eastern Bengal, and more particularly, Sylhet and its adjoining Cachar, constituted large numbers of Muslim populations and ecologically and geographically comprised a distinct region characterized by the presence of large numbers of natural water bodies such as rivers and their tributaries, beels, and haors. The area received heavy annual rainfall along with devastating floods, resulting in the formation of huge marshland and swamps with forested hinterlands. It was mainly inhabited by the primitive fishing and boating communities, and a section of people remain dependent on fishing and hunting even after the beginning of agriculture. The Turko-Afghan rulers, after occupation of the region, assisted by forest pioneers, ushered in a new era of economic transformation, leading to the far-reaching consequences and rapid expansion of Islam. The Turko-Afghan rulers, moved by their search for revenue, entrusted the task of expansion of agriculture to the forest pioneers, or sufi-saints, who mobilized the local population to the agricultural activities, leading to the emergence of village communities capable of paying revenue and loyal to the state. Therefore, the indigenous population of the region underwent gradual peasantization. Along with this, the medieval Muslim state also allotted land for the establishment of religious institutions like mosques, khanqahs, and shrines instrumental for disseminating Islam among the agrarian villages and communities. The Cachar region bordering Sylhet, which remained under tribal rule, was deeply influenced by this demographic transformation as a consequence of wanton migration of people and activities of Sufi saints. A critical re-examination of the spread of Islam in the Sylhet-Cacahr region will perhaps provide deep insight into the issue of conversion to Islam in the region.